1976
DOI: 10.1007/bf01927588
|View full text |Cite
|
Sign up to set email alerts
|

Developmental characteristics of histamine methyltransferase and phenylethanolamine-N-methyltransferase of rat brain

Abstract: The specific activity of histamine methyltransferase of rat brain increases rapidly from the 16th until the 25th day of gestation (7 days after birth). The specific activity of phenylethanolamine-N-methyl-transferase shows a rapid increase during the 1st and the 2nd week after birth, the adult values being obtained by the end of the 2nd week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

1978
1978
1984
1984

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…1 B). These results are in agreement with Kouvelas et al (1976), who reported a postnatal increase in rat brain HMT activity that peaked at day 10. These authors suggested that the decline in postnatal HA (such as shown in Fig.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…1 B). These results are in agreement with Kouvelas et al (1976), who reported a postnatal increase in rat brain HMT activity that peaked at day 10. These authors suggested that the decline in postnatal HA (such as shown in Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Correlations of HA and t-MH levels support this, since on these days significant correlations were found in all fractions except P,. Absence of correlation in the P, fraction may be due to its low HMT activity (Kouvelas et al, 1976). Such findings support the suggestion that HA leaves the PI fraction prior to its methylation.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…It is unlikely that this moderate response may be due to a high activity of HA-N-methyltransferase (HMT), the enzyme that inactivates HA in brain since in two separate studies a constant brain HMT activity which is similar to the adult, was found in rats from the 7th postnatal day (Martres et al, 1975;Kouvelas et al, 1976). Another aspect, maturation of the brain histaminergic system, remains to be briefly discussed.…”
Section: Discussionmentioning
confidence: 93%